STRATEGI PEMBELAJARAN TERPADU MENYIMAK DAN BERBICARA DI PERGURUAN TINGGI - Iqbal Iqbal (Universitas Negeri Makassar, 2012)
This study aimed to describe the planning, the implementation, and evaluation of the implementation of integrated learning strategies to improve student learning of listening and speaking. The research design is a classroom action research. Data was obtained from one teacher, and 40 sophomore students of Indonesia Language Education Department of Muhammadiyah STKIP in Bone. The research results showed that; (1) the planning of integrated learning strategies can improve the students learning of listening and speaking. (2 ) the implementation of integrated learning strategy can improve students learning of listening and speaking. Implementation steps were included; listening in pairs and cooperative learning, (3) evaluation of the integrated learning strategy can improve students learning of listening and speaking. It should be in line with the context of the content, real and factual.